The blind spot of online creative idea generation studies: A perspective of media materiality - Liu, Siyu; Ji, Feng; Zeng, Cen (Frontiers in Psychology, 2022)
Online creative idea generation is often considered an extension of traditional creative idea activities on the Internet platform, in which digital technology plays an important role. Consistent with the studies on traditional creative idea activities, the studies on online creative idea generation take the creativity of mass psychology as the core, and believe that digital technology can stimulate people’s creative output. This study challenges the past research paradigm from the perspective of media materiality, redefines the processes and activities of online creative idea generation, and further suggests that it may affect people’s psychology by reducing their creativity without real awareness. The study is innovative in both theory and practice. We also discuss the limitations and future directions of the study.